School, family and type 1 diabetes: meanings produced by pancreatic mothers (Research, Society and Development, 2022)
This article is an excerpt from the Master's dissertation research, in progress, linked to the Stricto Sensu Postgraduate Program in Teaching UNIC-IFMT, whose central theme is the meanings produced by the actors involved in the teaching-learning process of children. with type 1 diabetes mellitus, elementary school students from public schools in Cuiabá-MT. Diabetes is a chronic disease whose incidence occurs predominantly in childhood and youth, which increases every year, but which is still unknown by Brazilian schools. The purpose of this article is to reflect on the meanings produced by Pancreatic Mothers, the main caregivers of children with DM1, on the school-family relation and its effects on these students' learning. The methodology adopted for this study is of a qualitative approach, of a socio-discursive interactionist nature, through the investigation of the production of meanings enunciated by the discursive practices of the participants. The partial results show that school institutions have not offered the necessary assistance for the full development of students with DM1, overloading the Pancreatic Mothers physically and emotionally. It is expected, with this study, to raise the discussion about the importance of developing public policies aimed at students with special health conditions, but who do not fit into the target audience served by special education.